2012
DOI: 10.1186/1472-6815-12-13
|View full text |Cite
|
Sign up to set email alerts
|

Allergic rhinitis and its associated co-morbidities at Bugando Medical Centre in Northwestern Tanzania; A prospective review of 190 cases

Abstract: BackgroundAllergic rhinitis is one of the commonest atopic diseases which contribute to significant morbidity world wide while its epidemiology in Tanzania remains sparse. There was paucity of information regarding allergic rhinitis in our setting; therefore it was important to conduct this study to describe our experience on allergic rhinitis, associated co-morbidities and treatment outcome in patients attending Bugando Medical Centre.MethodsThis was descriptive cross-sectional study involving all patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Moreover, Said et al (2012), in a study in Tanzania, noticed that 92.6% of patients with AR had adenoidal hypertrophy, hypertrophy of nasal subordinate turbinates, nasal polyps, tonsillitis, otitis media, and sinusitis, as the most prevalent comorbidities (20). In our study on children aged 1 to 17 years, 16.6% of patients with adenotonsillar hypertrophy had AR.…”
Section: Discussionsupporting
confidence: 44%
“…Moreover, Said et al (2012), in a study in Tanzania, noticed that 92.6% of patients with AR had adenoidal hypertrophy, hypertrophy of nasal subordinate turbinates, nasal polyps, tonsillitis, otitis media, and sinusitis, as the most prevalent comorbidities (20). In our study on children aged 1 to 17 years, 16.6% of patients with adenotonsillar hypertrophy had AR.…”
Section: Discussionsupporting
confidence: 44%
“…16 Four articles investigating different therapeutic approaches did not address olfactory function as an outcome parameter but only mentioned smell or taste under potential adverse events. [17][18][19][20] Six articles included patients with AR and non-AR and did not provide a separate analysis for the subgroup of patients with AR. [21][22][23][24][25][26] Two articles were excluded because they only assessed the immediate effects of an allergic challenge, therefore providing little clinical information.…”
Section: Search Resultsmentioning
confidence: 99%
“…In addition, symptoms brought by AR such as apnea and snoring were also considered to be risk factors for sleep-disordered breathing events and contributed to the development of OSA. [61] In addition, some studies had demonstrated that several chemical mediators and inflammatory cytokines play interaction roles between AR and OSA, including histamine, cysteinyl leukotrienes (cysLTs), interleukin-1β(IL-1β), and interleukin-1 (IL-4) and so on. [58,62] Given the impact of AR to OSA, it seemed logical to investigate their relationship which may help understand overlapped subjects.…”
Section: Discussionmentioning
confidence: 99%
“…[63] Adenotonsillar hypertrophy (AH) was a common comorbidity of pediatric AR, it was reported that 92.6% of AR children also suffered AH . [61] Furthermore, AH is the main cause of OSAS for children aged 3 to 6, yet adults patients were often caused by obesity. [64] This meta-analysis showed no significant difference in the prevalence of AR in OSA and non-OSA patients (children and adults).…”
Section: Discussionmentioning
confidence: 99%